A review of social disinhibition after traumatic brain injury. Issue 2 (30th September 2016) - Osborne‐Crowley, Katherine; McDonald, Skye
Abstract : Acquired social disinhibition refers to a debilitating behavioural syndrome commonly reported after a severe traumatic brain injury (TBI) and is characterized by inappropriate social behaviour, often described as immaturity and insensitivity towards others. These behaviours can have enduring effects on the social capability of the individual and their relationships with others. However, research into socially disinhibited behaviour after TBI has been thwarted by a lack of consensus in the literature on definition and measurement. This review provides an overview of our current understanding of the definition, measurement, prevalence, associated outcomes, neuropathology, and underlying mechanisms of social disinhibition after TBI. In addition, suggestions are made for future research to further our understanding of this syndrome with the eventual aim of rehabilitating problematic behaviours. It is concluded that an improved understanding of what causes disinhibited behaviour after TBI will be necessary for the development of effective treatment strategies aimed at the rehabilitation of underlying impairments.